Efforts To Improve Students' Ips Learning Outcomes Through Problem Based Learning Models In Smp Negeri 2 Lubuk Alung - Rita Azwar; Muhammad Zulfadli; Andi Tenri Sumpala (Social Landscape Journal, 2022)
This study aims to disclose information and discuss the Efforts to Improve Student Social Studies Learning Outcomes through Problem Based Learning (PBL) Learning Models at SMP Negeri 2 Lubuk Alung. This type of research is classroom action research (CAR). This research was conducted at SMP Negeri 2 Lubuk Alung Jln. Tapian Puti No. 15 Lubuk Alung, Padang Pariaman Regency. The subjects of this study were students of class VII.1 of SMP Negeri 2 Lubuk Alung, Padang Pariaman Regency, totaling 32 people. This research was conducted in the odd semester of the 2021/2022 academic year. The research procedure consisted of two cycles with each cycle having two meetings. Each cycle consists of four stages of research, namely planning, implementation, observation and reflection. Data collection in this study was carried out using field notes, student worksheets, written tests, and documentation. The data analysis technique uses the percentage formula. The results of this study indicate that the Problem Based Learning (PBL) learning model has a positive impact on improving students' social studies learning outcomes. This can be seen from students' understanding and mastery of the material that has been delivered by the teacher so far (mastery learning increased from Pre-cycle, Cycle I and Cycle II, which were 19%, 37% and 81%.